The story of ginger bread heritage house: Phrae, Northern Thailand - Manissaward Jintapitak (2018)
© 2017 American Scientific Publishers All rights reserved. Following Western colonization in South-East Asia during the early 19th century, the demand of wood as a basic material for constructing the transportation infrastructure was higher than ever before. During that time, European timber business companies and Phrae rulers and their high ranking officers became very wealthy from their logging business. Teak, a durable wood was higher priced. Ginger-bread style housing was always regarded as a status symbol of the local elites in Phrae. Ginger-bread style demonstrates the relationship between Lanna arts and crafts and Victorian architectural style, first introduced in Myanmar by the British Raj and spread to Lanna Kingdom afterwards. Te influence of Chinese art and craft techniques on modern Lanna style also appear. In Phrae, there is a number of existing heritage houses waiting to be admired. Encouraging the story of the gingerbread house, inspiring people in the city, so that homeowners maintain and preserve the gingerbread house, and to provide an alternative to the creation of contemporary architecture for modern applications, ginger bread style homes became an adapted East-West fusion style of Phrae Province. Conservation is carried out with the involvement of all parties to bring about a sustainable well-being of people living in the city. When local people are proud and take care about their valued heritage houses attractive for tourism and the city’s economy grows, it can be a model for the future development of the old town appreciation.